Influence of amino acids and vitamins on the growth of gdhA derivative Pasterurella multocida B:2 for use as and animal vaccine - Oslan, Siti Nur Hazwani; Tan, Joo Shun; Saad, Mohd Zamri; Halim, Murni; Mohamed, Mohd Shamzi; Ariff, Arbakariya (Springer, 2019)
Pasteurella multocida serotype B:2 is the causative agent of haemorrhagic septicaemia, a fatal disease in cattle and buffaloes. For use as a vaccine in the treatment of HS disease, an efficient cultivation of attenuated gdhA derivative P. multocida B:2 (mutant) for mass production of viable cells is required. In this study, the role of amino acids and vitamins on the growth of this particular bacterium was investigated. Initially, three basal media (Brain–heart infusion, Terrific broth, and defined medium YDB) were assessed in terms of growth performance of P. multocida B:2. YDB medium was selected and redesigned to take into account the effects of amino acids (glutamic acid, cysteine, glycine, methionine, lysine, tyrosine, and histidine) and vitamins (vitamin B1, nicotinic acid, riboflavin, pyridoxine, pantothenic acid, and biotin). High viable cell number was largely affected by the availability of micronutrient components and macronutrients. Histidine was essential for the growth whereby a traceable amount (20 mM) was found to greatly enhance the growth of gdhA derivative P. multocida B:2 mutant (6.6 × 109 cfu/mL) by about 19 times as compared to control culture (3.5 × 108 cfu/mL). In addition, amongst the vitamins added, riboflavin exhibited the highest impact on the viability of gdhA derivative P. multocida B:2 mutant (5.3 × 109 cfu/mL). Though the combined histidine and riboflavin in the culture eventually did not promote the stacking impact on cell growth and cell viability, nonetheless, they were still essential and important in either growth medium or production medium.